THE EFFECT OF GINGER WATER SOAKING IN THE FEET ON BLOOD PRESSURE REDUCTION IN THE ELDERLY WITH HYPERTENSION - Kheli Fitria Annuril; Wahyudi Ramadhan; Agung Riyadi; Erni Buston (Proceeding B-ICON, 2023)
One of the main causes of death worldwide and a risk factor for conditions like heart attack, stroke, diabetes, and renal disease is hypertension, a noncommunicable disease.The purpose of this study was to find out how warm red ginger water foot soaks affected blood pressure in senior people with hypertension at PuskesmasPasar Ikan in Bengkulu City in 2021. The study used a control group design, pre- and post-tests, and a quasi-experimental methodology. The method of successive sampling was employed to gather the data, and a sample of 30 people was split into two groups, each of which was further subdivided into 15 individuals. The control group had a warm water foot bath, whereas the intervention group received a 15-minute foot bath with warm red ginger water over three days. T-test analysis was performed with a significance threshold of 0.05. Prior to the heated red ginger water foot bath, the intervention group's average systolic and diastolic blood pressure readings were 159.80/94.73 mmHg and fell to 140.33/84.67 mmHg. The average systolic and diastolic blood pressure in the control group. The results indicated statistically significant variations in systolic and diastolic blood pressure, both with p-values of 0.000. According to the study, senior hypertension patients benefit from a warm red ginger foot soak because it lowers blood pressure.